Konstruksi Berita Pemecatan Dosen Bercadar Di IAIN Bukittinggi (Analisis Framing Zhondang Pan dan Gerald M. Kosicki Konstruksi antara Kedisiplinan atau Cadar Pada Media Tribun, Viva dan Republika) - Uky Firmansyah (Universitas Islam Negeri Imam Bonjol Padang, 2019)
News Dr. Hayati Syafitri S, S M.Pd, a lecturer who was fired from a Civil Servant. This news was warmed by the public because the issue of dismissal was reported that Hayati Syafiti was wearing a veil or caused discipline. The online media informs variously about the issue of the dismissal of Dr. Dr. Hayati Syafitri SS, MPd, where the selected media are Tribun, Viva and Republika as different media in reporting the event. The Tribune packed the news The dismissal was caused by not working. Syafitri observed while the VIVA media in framing the news pointed out that Hayati, a Bukittinggi IAIN lecturer, was stopped because the veil polemic was the main reason and Republika in framing the news to readers by informing Hayati that Syafitri had been dismissed because of the problem. this directs the reader in dismissal there are irregularities